Spiritual Values and Social Capital Based Individual Empowerment in the Implementation of Disaster-Resilient Schools - Priyanto; Nevrettia Christantyawati; Wiwiek Harwiki (The Journal of Indonesia Sustainable Development Planning, 2026)
Schools are highly vulnerable to disaster risks, making the strengthening of the Disaster Safe School Program (SPAB) essential for developing resilient human resources. However, its implementation remains largely emphasized by technical and structural measures, with limited attention to individuals as active subjects of safety. This study examines how individual empowerment is developed through spiritual values and social capital in a pesantren-based school context using a qualitative case study approach, combining focus group discussions and participatory observation. The findings reveal that empowerment emerges progressively through the internalization of spiritual values, active engagement in disaster- related practices, and the reinforcement of social relationships within the school community. Spiritual values foster a sense of security and moral agency, while social capital sustains participation and collective preparedness. This study contributes to policy by proposing the integration of value-based empowerment indicators and participatory learning mechanisms into SPAB frameworks. These findings provide actionable insights for policymakers to shift from compliance-based evaluation toward human-centered disaster education approaches.